A new species of planthopper in the genus Myconus (Hemiptera: Auchenorrhyncha: Fulgoroidea: Achilidae) from the Osa Peninsula in Costa Rica - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2024)
Recent surveys of palm-associated planthoppers in Costa Rica have revealed many new species, primarily in the families Derbidae and Cixiidae, but also Myconus jacquelinae Bahder & Bartlett, in the Achilidae. Here a new species of Myconus from the the Osa peninsula is described as Myconus florae sp. n. with supplemental molecular data for the barcoding region (5’-half) of the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene, and histone 3 (H3) gene. A key to all species of Myconus is provided.